2022
DOI: 10.1016/j.physd.2022.133158
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the dynamics of COVID-19 infection and mortality in the United States, India, and Brazil

Abstract: This paper compares and contrasts the spread and impact of COVID-19 in the three countries most heavily impacted by the pandemic: the United States (US), India and Brazil. All three of these countries have a federal structure, in which the individual states have largely determined the response to the pandemic. Thus, we perform an extensive analysis of the individual states of these three countries to determine patterns of similarity within each. First, we analyse structural similarity and anomalies in the traj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The analysis of several cases studies within a larger region provides spatial dynamics concerning virus spread. The chosen federative units for the study are known to be heterogeneous among each other 35 37 since Brazil is a large country where there were several different outbreaks dates, local government policies, and population behavior. Brazilian spatial epidemic progression studies 35 , 36 indicated multiple initial outbreaks spread progressively to neighboring territories.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The analysis of several cases studies within a larger region provides spatial dynamics concerning virus spread. The chosen federative units for the study are known to be heterogeneous among each other 35 37 since Brazil is a large country where there were several different outbreaks dates, local government policies, and population behavior. Brazilian spatial epidemic progression studies 35 , 36 indicated multiple initial outbreaks spread progressively to neighboring territories.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Such methodologies have been applied to a wide variety of asset classes including equity markets [11], FX markets [19], cryptocurrencies [20,21,22,18,23,24,25,26,27,28,29,30,31,32,33] and debt-related instruments [34]. There is a litany of work where such techniques have been used in other domains including COVID-19 [35,36,37], extreme human behaviours [38] and epidemiology. Readers interested in recent work related to temporal dynamics with various societal impacts on the economy should see [39,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis relies on a broad existing literature of time series analysis as used by applied mathematicians and statisticians. Such methods have been applied widely within the physical and social sciences, including epidemiology [27,28,29,30,31,32], finance [33,34,35,36,37,38], and other fields [39,40,41,42]. There are a variety of time series analysis frameworks that we draw upon, including parametric models [43,44], techniques built upon distance metrics and similarity, [45,46,47,48,49], network analysis [50,51,52], clustering [53], and others [54,55,56,57].…”
Section: Introductionmentioning
confidence: 99%